Historical review, catalog of type specimens and online database of the ichthyology collection of the Instituto de Ciencias Naturales of the Universidad Nacional de Colombia (ICN-MHN) - Mojica, José Ivan; Agudelo-Zamora, Henry D. (Zootaxa, 2018)
For the first time, the catalog of type specimens of ICN-MHN is presented with high resolution photographs. The catalog lists 87 species in 161 lots and includes 41 holotypes, 3 neotypes, and 117 lots of paratypes. Some doubts remain about type specimens of some species described by Miles and Dahl that were supposedly deposited at ICN-MHN. The history of the collection is reconstructed and valuable specimens once considered lost or destroyed have been rediscovered. The botanical and zoological collections of the ICN can be consulted online (http://www.biovirtual.unal.edu.co).